In-situ X-ray tomography analysis of the evolution of pores during deformation of AlSi10Mg fabricated by selective laser melting - Samei, Javad; Amirmaleki, Maedeh; Shirinzadeh Dastgiri, Mohammad; Marinelli, Carlo; Green, Daniel E. (Materials letters, 2019)
[Display omitted] •AlSi10Mg fabricated by SLM subjected to uniaxial tension coupled with X-ray tomography.•3D XCT models of the specimen were made at 5 different strains prior to, and after, fracture.•Pore vol%, density, and growth was quantified as a function of true plastic strain.•Significant coalescence of pores occurred before fracture. AlSi10Mg is an interesting structural material due to its high specific mechanical properties, and good weldability which makes it a good candidate for additive manufacturing by selective laser melting. In this paper, the evolution of pores is visualized and quantified in an AlSi10Mg fabricated by selective laser melting using in-situ tension coupled with X-ray computed tomography. Graphical models were produced in order to visualize the evolution of pores, and the volume fraction, density, and mean diameter of pores were determined at each stage of deformation. Significant coalescence of pores was found during post-uniform elongation. Dimples on the fracture surfaces indicate ductile fracture.